7. ECONOMIC BURDEN ANALYSIS OF RESPIRATORY DISEASES AT LE VAN THINH HOSPITAL FROM 2018 TO 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: This study aims to analyze the economic burden of treating respiratory diseases at Le Van Thinh Hospital (BVLVT) over the period from 2018 to 2023.Methods: A cross-sectional descriptive study was conducted by retrospectively collecting comprehensive cost data related to respiratory disease treatments at BVLVT from 2018 to 2023. Data were gathered through total sampling, including patients with health insurance and primary diagnosis codes from J00 to J99 according to ICD-10 classification, to aggregate and analyze treatment costs.Results: From 2018 to 2023, the total expenditure for treating respiratory diseases was 211.919 billion VND, with inpatient treatment costs accounting for 50.8% of the total. Among the two disease groups with the highest costs, 93.1% of the expenses for influenza and pneumonia were for inpatient treatment, while 93.6% of the expenses for acute upper respiratory infections were for outpatient treatment. In outpatient treatment, the cost for acute respiratory infections showed an increasing trend, from 8.175 billion VND in 2018 to 14.164 billion VND in 2023. In inpatient treatment, the costs for influenza and pneumonia, the highest-cost disease group, increased from 7.512 billion VND in 2018 to 18.624 billion VND in 2023. Among the components of direct medical costs, drug costs were consistently the highest each year and showed an increasing trend, ranging from 58.9% to 60.7% annually.Conclusion: This study provides a comprehensive overview of common diseases and trends in disease patterns across inpatient and outpatient settings, and among different age groups including children, adults, and the elderly. These findings offer a scientific basis for LVTH to adjust its drug list structure, develop more effective healthcare strategies, allocate resources reasonably, and enhance the quality of medical services for the regional population.
Keywords: Disease patterns, disease trends, Le Van Thinh Hospital, Covid-19